"Leaning In" or "Taking a Knee": Career Trajectories of Senior Leaders in the Canadian Armed Forces. Issue 3 (July 2023) - Coulthard, Julie; Wright, Justin
Less research has examined the extent to which external contexts and factors that influence an organizational member's life choices also influence their career trajectories within the military, and particularly among those who advance to leadership positions at the General Officer/Flag Officer level. Interviews were conducted with 20 select General Officer/Flag Officers in the Canadian Armed Forces. As part of a secondary analysis of an exploratory qualitative study, we applied a Life Course Theory lens to better understand the intersections between the sociohistorical and cultural context of senior leader development, and the individual choices that the participants made that led to their ascent to their rank. This study provides insight into how the historical time and place, the timing in their lives, the linked lives they share with family, and the degree of agency they maintained over their life choices led participants to "lean in" rather than "take a knee."